(untitled) (Journal of Educational and Psychological Sciences, 2018)
The purpose of this quasi-experimental research study is to determine the effects of a software program, specifically "Fractions v2.0", when it is used as a supplemental tool to traditional math instruction as compared to using only traditional math instruction in fourth grade classrooms in order to enhance the understanding of fractions deeply and effectively. A total of 115 of fourth grade students participated in the project. The study occurred during a four-week time frame in eight public elementary schools in Abha, Saudi Arabia. Pre-and post-tests were used for data collection. Findings revealed that use of Fractions v2.0 as a supplement to traditional math instruction would lead to an improvement in Knowledge, Comprehension, Application, Analyzing, Creating, and Evaluating scores. Also, findings revealed that improvement in lower-order thinking scores did not differ significantly across conditions, F(1, 113) = .00, p = .988, while they improved across time F(1, 113) = 4044.61, p < .001. In addition, findings revealed that improvement in higher-order thinking scores did not differ significantly across conditions, F(1, 113) = .05, p = .828, while they improved across time, regardless of condition, F(1, 113) = 2831.83, p < .001.